2002
DOI: 10.4049/jimmunol.169.11.6482
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-13 in Established Allergic Airway Disease

Abstract: The effectiveness of targeting IL-13 in models where airway hyperresponsiveness (AHR) and airway inflammation have already been established is not well-described. We investigated the effects of blocking IL-13 on the early and late phase airway responses and the development of AHR in previously sensitized and challenged mice. BALB/cByJ mice were sensitized (days 1 and 14) and challenged (days 28–30) with OVA. Six weeks later (day 72), previously sensitized/challenged mice were challenged with a single OVA aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 44 publications
(66 reference statements)
12
135
1
2
Order By: Relevance
“…50 In experimental asthma models, airway hyperreactivity accompanied by high levels of IL-4 and IL-5 secretion can be induced in intact but not IL-13À/À mice. 51,52 Sensitized animals can be protected by treatment with IL-13Ra-chain constructs, 53 and although the IL-4Ra-chain may be involved, this is disputed. 46,49 Mice whose Th1 system is crippled by the genetic disruption of T-bet expression develop spontaneous asthma-like disease, which is accompanied by high numbers of CD44 and CD69 bright CD4 þ T cells; again, this condition can be ameliorated by the direct blockade of IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…50 In experimental asthma models, airway hyperreactivity accompanied by high levels of IL-4 and IL-5 secretion can be induced in intact but not IL-13À/À mice. 51,52 Sensitized animals can be protected by treatment with IL-13Ra-chain constructs, 53 and although the IL-4Ra-chain may be involved, this is disputed. 46,49 Mice whose Th1 system is crippled by the genetic disruption of T-bet expression develop spontaneous asthma-like disease, which is accompanied by high numbers of CD44 and CD69 bright CD4 þ T cells; again, this condition can be ameliorated by the direct blockade of IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of both IL-13 and IL-4 membrane-bound heterodimeric receptors induces receptor molecule dimerization and activation of the Janus family members of inner membrane-bound tyrosine kinases, which then phosphorylate and initiate the nuclear transport of STAT-6 transcription factors [9]. However, studies in murine models of asthma have indicated that IL-13 rather than IL-4 appears to be critical for the development of allergic airway inflammation, hyperresponsiveness and matrix remodeling in asthma [30][31][32][33][34][35]. In the present study, we observed that overexpression of c-Maf, in the absence of a coincident overexpression of GATA-3, but in the presence of IL-2, down-regulates IL-13 but not IL-4 production in developing and polarized lung CD4 + T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of total IgE, OVA-specific IgE, IgG1, and IgG2a were measured by ELISA as previously described (29). The anti-OVA Ab titers of samples were related to internal pooled standards that were generated in the laboratory and expressed as ELISA units.…”
Section: Measurement Of Total and Ova-specific Absmentioning
confidence: 99%
“…Cytokine levels in the BAL fluid and cell culture supernatants were measured by ELISA as previously described (29). IFN-␥, IL-4, IL-5, IL-10, IL-12 (BD PharMingen, San Diego, CA), and IL-13 (R&D Systems, Minneapolis, MN) ELISAs were performed according to the manufacturer's directions.…”
Section: Measurement Of Cytokinesmentioning
confidence: 99%